2022
DOI: 10.3390/biomedicines10102618
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Assessment of pNET and NELM after Everolimus by Quantitative MRI Parameters

Abstract: Assessment of treatment response to targeted therapies such as everolimus is difficult, especially in slow-growing tumors such as NETs. In this retrospective study, 17 patients with pancreatic neuroendocrine tumors (pNETs) and hepatic metastases (NELMs) (42 target lesions) who received everolimus were analyzed. Intralesional signal intensities (SI) of non-contrast T1w, T2w and DCE imaging, and apparent diffusion coefficients (ADCmean and ADCmin) of DWI, were measured on baseline and first follow-up MRI after e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…These observations might be related to the small number of total pNET (n = 16). Another possibility is that functional / morphological changes might be different between liver metastasis and the primary tumor as discussed by Ingenerf et al 28 The Choi et al response criteria suggested that changes in tumor attenuation could better represent treatment response to imatinib in gastrointestinal stromal tumors. 29 While Choi et al found a decrease in tumor density of more than 15% on CT had a sensitivity of 97% and a specificity of 100% in identifying PET responders versus 52% and 100% by RECIST, we observed a slight, but statistically significant decrease in HU values in nonresponding lesions (p = 0.02), while no significant change was observed in responding lesions.…”
Section: Discussionmentioning
confidence: 99%
“…These observations might be related to the small number of total pNET (n = 16). Another possibility is that functional / morphological changes might be different between liver metastasis and the primary tumor as discussed by Ingenerf et al 28 The Choi et al response criteria suggested that changes in tumor attenuation could better represent treatment response to imatinib in gastrointestinal stromal tumors. 29 While Choi et al found a decrease in tumor density of more than 15% on CT had a sensitivity of 97% and a specificity of 100% in identifying PET responders versus 52% and 100% by RECIST, we observed a slight, but statistically significant decrease in HU values in nonresponding lesions (p = 0.02), while no significant change was observed in responding lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Parameters such as signal intensity (SI) on T1-weighted or T2-weighted images, tumor vascularization, and apparent diffusion coefficient (ADC) derived from DWI are increasingly scrutinized for their predictive and monitoring potential across various therapy regimens. 8 , 9 , 10 , 11 Notably, no prior study has assessed the utility of these MRI parameters for monitoring therapy or predicting CAPTEM response in patients with hepatic metastasized NETs. Therefore, this study aims to evaluate clinical, morphological, and functional imaging factors for their ability to predict and monitor therapy response in metastatic NET patients undergoing CAPTEM treatment.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that there are differences between pNET and its metastases: ADCmin values of NELM decreased significantly in responders following the initiation of everolimus treatment, whereas ADC values in nonresponders increased. Conversely, ADC (both minimum and mean) of pNETs tended to increase in responders, while there was no change observed in nonresponders, indicating distinct behavior between pNETs and their NELM counterparts ( 19 ).…”
Section: Introductionmentioning
confidence: 99%